Development of Interactive Multimedia Based on Appy Pie to Improve Learning Outcomes of Elementary School Students - Zikri Wildan Setiadi; Aldina Eka Andriani (Postgraduate, University of Mataram, 2024)
This research aims to develop, test the feasibility and effectiveness of interactive multimedia based on Appy Pie to improve the cognitive learning outcomes of students in grade V of SD Negeri Kemijen 02, Semarang City. This type of research is development research (R&D) using the ADDIE model. The subjects of the study were 27 students in grade V of SD Negeri Kemijen 02. Data collection techniques include non-test and test. The data analysis technique uses normality test, homogeneity test, t-test, and N-Gain test. The results showed that the Appy Pie-based interactive multimedia development included covers, instructions for use, concept maps, learning competencies, materials, videos, discussion pages, AI chatbots, and evaluations. The feasibility results of media experts are 97.91%